Assessment of the knowledge of CT technologists regarding radiation protection and computed tomography parameters in Libya - Nureddin Musa; Inas. A. Elderbali; Seham. M. Hafed (Libyan Journal of Medical and Applied Sciences, 2025)
To evaluate the knowledge of CT technologists about radiation protection as well as CT parameters and their impact on image quality and patient dose. This cross-sectional descriptive-analytic study was performed in 11 government hospitals from different cities, Libya, was conducted between April and September 2025, using a valid and reliable online questionnaire consisting of 18 questions assigned to 150 CT technologist. Each questionnaire contained demographic characteristics along with CT parameters including mAs, pitch, scan time, automatic tube current modulation, image construction technique and effects of these parameters on image quality and radiation dose. There were statistically significant differences in the level of knowledge among CT technologists regarding radiation protection and specialized training, with 73% reporting that they had not received any training in this regard. As for knowledge of the device's parameters and their relationship to image quality and patient dose, 74% of them reported that they had not received any training on this subject, and the results showsa significant difference in the mean mAs (1.09±0.288, P<0.005 ), pitch(1.21±0.409, P<0.005), ATCM (1.39±0.490,P<0.05)and image reconstruction(1.15±0.339, P<0.005). The overall familiarity of CT technologists about radiation protection and scan parameters which affecting image quality, dose or both was found insufficient. In this case, retraining update courses should be offered frequently to augment and refresh the knowledge of technologists. which can contribute to reducing exposure for patients, CT staff and community at the same time.